Identification of active compounds and antioxidant activity of teak (Tectona grandis) leaves - Venty Suryanti; TRIANA KUSUMANINGSIH; SOERYA DEWI MARLIYANA; HILDA ALFIANI SETYONO; ELYNA WAHYU TRISNAWATI (Society for Indonesian Biodiversity, 2020)
Abstract. Suryanti V, Kusumaningsih T, Marliyana SD, Setyono HA, Trisnawati EW. 2020. Identification of active compounds and antioxidant activity of teak (Tectona grandis) leaves. Biodiversitas 21: 941-947. Teak (Tectona grandis) grows in tropical area and the teak wood is widely used for building construction and furniture. Young teak leaf contains red pigment and often are used for natural food coloring. The research objectives were to isolate the young teak leaf chemical compounds and to investigate their antioxidant activities. The compounds identification was carried out by UV-Vis Spectroscopy, GC-MS and LC-MS. The antioxidant activity determination was carried out by 2,2-diphenyl-1-picryl-hydrazyl-hydrate (DPPH) method. The total phenolics content was determined using Folin-Ciocalteu method and total anthocyanins content was examined using the H-differential method. Two fractions were observed further by UV-Vis Spectroscopy, GC-MS and LC-MS. The UV-Vis spectrum of FA confirmed the presence of anthocyanins which has maximum absorbance at 208 and 492 nm. The GC-MS spectrum of fraction A (FA) revealed 4-hydroxy-4-methyl-2-pentanone, glycerin monoacetate, glycerin diacetate and 1-eicosanol. The UV-Vis spectrum of FC also confirms the presence of anthocyanins which has maximum absorbance at 489 nm. The LC-MS spectrum of fraction C (FC) shows anthocyanins, namely malvidin-3-o- (6-o-acetyl)-5-o-diglucoside. The FA and FC teak leaf fractions have strong antioxidant activities as their IC50 values are less than 50 ppm. Total phenolic of teak leaf extract was 6.17 mg GAE/g and total anthocyanins of teak leaf extract were 67.5 mg/L.